Jak Mikołaj z Błonia czytał i wplatał Roberta Holcota do swoich tekstów? : Glosa nad przekładem kazania pneumatologicznego i ślubnego - Regulska, Anna (Przegląd Tomistyczny, 2025)
The article explores how Nicholas of Błonie, Polish preacher, canon lawyer, and author of a handbook for priests, made use of the Commentary on the Book of Wisdom by the English preacher and Dominican Robert Holcot. The analysis focuses on two sermons by Pszczółka, whose translation is scheduled for publication in 2026: the one for Pentecost and the one for the Second Sunday after Epiphany. These examples illustrate various methods of drawing on Holcot’s Commentary on the Book of Wisdom, adapting it to a new context, and the gradual disappearance of Holcot’s name in this process. These findings may prove useful not only to scholars studying the works of both authors, but also more broadly to translators and editors of medieval texts.